Thurrock's deeper past : a confluence of time : the archaeology of the borough of Thurrock, Essex, from the last Ice Age to the establishment of the English kingdoms - Tripp, Christopher John, (Archaeopress Publishing Ltd, 2018)
This volume looks at the evidence for human activity in Thurrock and this part of the Thames estuary since the last Ice Age, and how the river crossing point here has been of great importance to the development of human settlement and trade in the British Isles.